Development of nano-crystalline ceramic laser materials and high power diode pumped ceramic lasers - Tang, Ding Yuan. (2012)
Solid-state lasers have been utilized for micromachining in the semiconductor industry; for welding, cutting, and drilling in the automotive, heavy machinery, and steel industry; for X-ray and laser-beam generation in medical applications [1, 2], and as a light source in nuclear fusion [3]. The applications of solid-state lasers and the laser market are rapidly growing. Solid-state lasers can be classified into crystal lasers and glass lasers [4]. The essential requirements on the media used as gain host in solid-state lasers are high thermal conductivity, chemical stability, and ease of machining, in addition, (a) a large product of σ (cross section of stimulated emission) and τ (fluorescence lifetime), (b)